(untitled) (MAUSAM, 1959)
Results of measurements of the size distribution of raindrops made at Poona during the months of August, September and October 1956, are reported in the form of a table showing the number of drops received at the ground level per m2 per sec for various ranges of diameter at 0.25 nterval, for different inten sities of precipitation ranging from 0 to 40 mm hr-l. Average values have been calculated and presented in the form of a similar table. Histograms showing the number, volume of liquid water, momentum and kinetic energy of raindrops per m2 per sec, against the raindrop diameters are given for six typical intensities of precipitation. The variation of the total number N, momentum M and kinetic energy E (in joules) of raindrops per m2 per sec with intensity of precipitation is shown graphically. By the method of least squares the following relations are obtained. N=710I0.47, M=165 I, and E = 2.8x10-3 I1.13, where I is the intensity of precipitation in mm hr-1.The results are presented in a form suitable for soil erosion problems. The data are confined to general rains.